Strengthening Students' Religious Character Through Culture at SD Muhammadiyah: Penguatan Karakter Religius Siswa Melalui Budaya di SD Muhammadiyah - Subagia, M. Nurhuda Ricky; Amrullah, Muhlasin (Journal of Islamic and Muhammadiyah Studies, 2024)
The General background strengthening students' religious character is crucial for cultivating individuals with strong moral values and behavior. Schools are responsible for integrating these values into the daily lives of students. Specific background SD Muhammadiyah 1 Krembung has actively implemented a religious character education program, aiming to instill positive habits such as prayer, gratitude, tolerance, and worship. Knowledge gap while various studies have focused on character education, few have explored the systematic implementation of religious character-building practices in elementary schools. Aims this study aims to examine how school culture, through habitual religious practices, can strengthen the religious character of students. Results the implementation of religious habits such as the 5S (Smile, Greet, Salute, Polite, and Courteous), regular prayers, and recitation has positively influenced the students' behavior, promoting religious values in their daily lives. Novelty the study highlights the structured approach to religious character education through habitual practices as a consistent and planned effort within the school’s culture. Implications the findings suggest that embedding religious values in daily school routines can significantly strengthen students’ religious character, providing a model for other schools seeking to implement similar programs. Highlights: Religious character education is integrated into daily school activities. The 5S approach (Smile, Greet, Salute, Polite, and Courteous) is key to promoting religious values. Consistent and planned religious practices positively influence student behavior. Keywords: Religious Character Education, School Culture, Elementary Students, Habitual Practices, Moral Values